2021
DOI: 10.3390/cancers13123092
|View full text |Cite
|
Sign up to set email alerts
|

B-Helper Neutrophils in Regional Lymph Nodes Correlate with Improved Prognosis in Patients with Head and Neck Cancer

Abstract: The role of neutrophils during cancer formation and elimination is diverse. Here, for the first time, we investigate neutrophil helper cells (NBH), their influence on B cell activity in the regional lymph nodes (RLN) of head-and-neck cancer patients and the effect of this neutrophil/B cell interaction on patient prognosis. Circulating and RLN neutrophils of patients with stage I–IV head-and-neck squamous cell carcinoma were investigated with flow cytometry and qPCR. In addition, neutrophil/B cell co-localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The increased expression of MHC class II on LN neutrophils in healthy organ donors was also demonstrated (Lok et al, 2019). Recently, we could also demonstrate the association between the infiltration of LNs by activated neutrophils and B cell responses in patients with HNC (Pylaeva et al, 2021). In animal models, co-culture of murine LN neutrophils stimulated with OVA-containing immune complexes and OVA-specific OT-II CD4 T cells resulted in increased expression of CD25 and CD69, early markers of T cell activation (Lok et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…The increased expression of MHC class II on LN neutrophils in healthy organ donors was also demonstrated (Lok et al, 2019). Recently, we could also demonstrate the association between the infiltration of LNs by activated neutrophils and B cell responses in patients with HNC (Pylaeva et al, 2021). In animal models, co-culture of murine LN neutrophils stimulated with OVA-containing immune complexes and OVA-specific OT-II CD4 T cells resulted in increased expression of CD25 and CD69, early markers of T cell activation (Lok et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…In many cancer entities, including head and neck cancer (HNC), high intra-tumoral neutrophil counts have been shown to be associated with a worse patient prognosis (4)(5)(6). Several responsible mechanisms have been identified, including the support of angiogenesis (7,8), the promotion of metastatic spread (9)(10)(11)(12), the regulation of B cell activation (13,14), as well as the regulation of T-cell responses in tumor tissue (15)(16)(17). Neutrophil tumorigenicity is regulated by tumor-derived factors, such as type I interferons (IFNs) (2,8,18,19), transforming growth factor beta (TGFb) (20), or granulocyte-colonystimulating factor (G-CSF) (21).…”
Section: Introductionmentioning
confidence: 99%
“…The activation-induced cytidine deaminase (AICDA) is an essential enzyme of the adaptive immune system. A recent study found that elevated expression of AICDA regulates the function of B cells in regional lymph nodes and significantly improves prognosis of HNSCC patients (Pylaeva et al, 2021). Tyrosine kinase 2 (TYK2), a member of the Janus kinase (JAK) family, has emerged as both a promising biomarker and a target for anticancer therapies (Borcherding et al, 2021).…”
Section: Discussionmentioning
confidence: 99%